THE TROJAN HORSE OF SPIRITUALITY: ART AS A STRATEGIC TOOL FOR TRANSFORMING POP CULTURE AND THE CONSUMER SOCIETY - Medina Akkaynak, (International Journal of Innovative Technologies in Social Science, 2025)
This article addresses the detrimental impact of consumer society (ecological crisis, social inequality, spiritual emptiness) and explores the potential of contemporary art as a vehicle for introducing spiritual values into popular culture and counteracting these negative aspects. The author examines the possibility of employing art as a “Trojan horse,” capable of bypassing superficial perception to “penetrate” societal consciousness and foster spiritual transformation. Particular attention is given to the role of spirituality in this process, and the necessity of returning to profound spiritual values through art that leaves a lasting impact on the viewer is substantiated. The article draws upon the ideas of prominent thinkers such as Erich Fromm, Jean Baudrillard, and Wassily Kandinsky, and proposes strategies and techniques for creating new trends in the art world based on the utilization of symbolism, the creation of meditative spaces, and appeals to universal values. The examples of Damien Hirst, Banksy, and Marina Abramović are analyzed in relation to the influence of the market on art and the commodification of spiritual themes, while James Turrell and Wolfgang Laib demonstrate alternative approaches rooted in profound spiritual expression. This study aims to reveal how art can serve as a means to introduce spiritual values into popular culture and counteract the negative consequences of consumerism.